Interaction of heparin and heparin-derived oligosaccharides with synthetic peptide analogues of the heparin-binding domain of heparin/heparan sulfate-interacting protein - Wang, Jing; Rabenstein, Dallas L. (Biochimica et biophysica acta, 2009)
Although protamine is effective as an antidote of heparin, there is a need to replace protamine due to its side effects. HIP peptide has been reported to neutralize the anticoagulant activity of heparin. The interaction of HIP analog peptides with heparin and heparin-derived oligosaccharides is investigated in this paper. Seven analogues of the heparin-binding domain of heparin/heparan sulfate-interacting protein (HIP) were synthesized, and their interaction with heparin was characterized by heparin affinity chromatography, isothermal titration calorimetry, and NMR. NMR results indicate the imidazolium groups of the His side chains of histidine-containing Hip analog peptide interact site-specifically with heparin at pH 5.5. Heparin has identical affinities for HIP analog peptides of opposite chirality. Analysis by counterion condensation theory indicates the peptide AC-SRPKAKAKAKAKDQTK-NH 2 makes on average ∼ 3 ionic interactions with heparin that result in displacement of ∼ 2 Na + ions, and ionic interactions account for ∼ 46% of the binding free energy at a Na + concentration of 0.15 M. The affinity of heparin for the peptides is strongly dependent on the nature of the cationic side chains and pH. The thermodynamic parameters measured for the interaction of HIP peptide analogs with heparin are strongly dependent on the peptide sequence and pH. The information obtained in this research will be of use in the design of new agents for neutralization of the anticoagulant activity of heparin. The site-specific binding of protonated histidine side chains to heparin provides a molecular-level explanation for the pH-dependent binding of β-amyloid peptides by heparin and heparan sulfate proteoglycan and may have implications for amyloid formation.